2002
DOI: 10.1038/sj.bjc.6600161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pathological tumour variables on long-term survival in resectable gastric cancer

Abstract: Although tumour stage and nodal status are established prognostic factors for resectable gastric cancer, the relative importance of other pathological characteristics remains unclear. This study reports univariate and multivariate analyses of the prognostic value of various pathological and staging factors based on 324 patients entered into the MRC randomised surgical trial for gastric cancer. In the univariate analysis tumour stage, nodal status, UICC clinical stage, number of involved nodes, WHO predominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…In this study there was a trend for better long-term survival for patients with intestinal types than those with diffuse-type adenocarcinoma of the stomach; however, in the multivariate analysis, T stage was the most significant predictor of survival, and histological subtype had no effect on survival. Cuschieri and Weeden have shown that histopathological subtypes such as the WHO predominant type, mixed Lauren type, Ming type, tumour differentiation and lymphocytic and tumour stromal eosinophilic infiltration were all found to have a significant impact on survival [11]. Our 5-year survival rate is lower than those reported in other studies, which may Fig.…”
Section: Discussioncontrasting
confidence: 76%
“…In this study there was a trend for better long-term survival for patients with intestinal types than those with diffuse-type adenocarcinoma of the stomach; however, in the multivariate analysis, T stage was the most significant predictor of survival, and histological subtype had no effect on survival. Cuschieri and Weeden have shown that histopathological subtypes such as the WHO predominant type, mixed Lauren type, Ming type, tumour differentiation and lymphocytic and tumour stromal eosinophilic infiltration were all found to have a significant impact on survival [11]. Our 5-year survival rate is lower than those reported in other studies, which may Fig.…”
Section: Discussioncontrasting
confidence: 76%
“…Indeed, high levels of intratumoral eosinophils have been associated with poor prognosis in two additional cohorts of HNC patients (n = 31 and n = 87), 331 , 332 but with improved disease outcome in a third HNC patient group (n = 25), yet only among subjects bearing epidermal growth factor receptor (EGFR) + lesions 333 . Along similar lines, tumor infiltration by eosinophils has been reported to constitute a positive prognostic indicator in cohorts of gastric carcinoma patients (n = 647 and n = 324), 334 , 335 glioma patients receiving a combinatorial immunotherapeutic regimen (n = 28), 336 subjects affected by lung adenocarcinoma (n = not available), 337 CRC patients (n = 126), 338 and subjects affected by cervical carcinoma treated with radiotherapy (n = 14) 339 …”
Section: Other Immune Cellsmentioning
confidence: 85%
“…This is akin to escaping a room full of assassins trained to kill you. Many researchers have shown the presence of intratumoral leukocytes in histologic tumor sections to be a favorable prognostic feature in breast cancer [88,89], lung cancer [90,91], colorectal cancer [92,93], stomach cancer [94,95], esophageal cancer [96,97], gallbladder cancer [98,99], malignant melanoma [100,101], neuroblastoma [102,103], cancers of the head and neck [104], prostate cancer [105], testis cancer [106,107], bladder cancer [108,109], and kidney cancer [110]. Unfortunately, the story is also obfuscated by a number of manuscripts that have shown the opposite effect in breast cancer [111,112], malignant melanoma [113,114], lung cancer [115,116], bladder cancer [117], and renal cell carcinoma [118,119].…”
Section: Tumor-infiltrating Leukocytesmentioning
confidence: 99%